PENGUBAHAN TINGKAH LAKU MALADJUSTMENT MENJADI ADJUSTMENT SISWA DI DALAM KELAS MELALUI LAYANAN “RATIONAL EMOTIVE BEHAVIOR THERAPY” (Studi Kasus Pada Siswa Kelas VIIIA SMP PGRI Kradenan Grobogan Tahun Pelajaran 2020/2021) - Risky Singgih Pamungkas (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
Abstract : This study aims to change students’ behavioral maladjustment into behavioral adjustment in the classroom using Rational Emotive Behavior Therapy. Applying qualitative paradigm, this study was conducted in SMP PGRI Kradenan. The data were collected using interviews and observations. Participants were two Class VIIIA students of SMP PGRI Kradenan who received information services. Technique triangulation was performed to ensure data validity. The descriptive qualitative data analysis was made using several stages: data collection, data display, data reduction, and drawing of conclusion. The interview and observation results concluded that students receiving rational emotive behavior therapy exhibited improvement, i.e., students exhibited more disciplined behavior and paid more attention to the teachers and did not disturb their classmates. Keywords : Qualitative research, Rational Emotive Behavior Therapy, Behavioral maladjustment, Behavioral Adjustment